Evaluating performance of National Hockey League players after a concussion versus lower body injury - Van Pelt, K. L.; Lapointe, A. P.; Galdys, M. C.; Dougherty, L. A.; Buckley, T. A.; Broglio, S. P. (Journal of Athletic Training, 2019)
Context Concussions elicit changes in brain function that may extend well beyond clinical symptom recovery. Whether these changes produce meaningful deficits outside the laboratory environment is unclear. The results of player performance postconcussion within professional sports have been mixed.